The Innate Immune Response in House Dust Mite-Induced Allergic Inflammation - Wang, Jiu-Yao (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2013)
Hypersensitivity to house dust mite (HDM; Dermatophagoides sp.) allergens is one of the most common allergic responses, affecting up to 85% of asthmatics. Sensitization to indoor allergens is the strongest independent risk factor associated with asthma. Additionally, >50% of children and adolescents with asthma are sensitized to HDM. Although allergen-specific CD4(+) Th2 cells orchestrate the HDM allergic response through induction of IgE directed toward mite allergens, activation of innate immunity also plays a critical role in HDM-induced allergic inflammation. This review highlights the HDM components that lead to activation of the innate immune response. Activation may due to HDM proteases. Proteases may be recognized by protease-activation receptors (PARs), Toll-like receptors (TLRs), or C-type lectin receptors (CTRs), or act as a molecular mimic for PAMP activation signaling pathways. Understanding the role of mite allergen-induced innate immunity will facilitate the development of therapeutic strategies that exploit innate immunity receptors and associated signaling pathways for the treatment of allergic asthma.